2013
DOI: 10.1016/j.febslet.2013.04.042
|View full text |Cite
|
Sign up to set email alerts
|

The most important thing is the tail: Multitudinous functionalities of intrinsically disordered protein termini

Abstract: a b s t r a c tMany functional proteins do not have well-folded structures in their substantial parts, representing hybrids that possess both ordered and disordered regions. Disorder is unevenly distributed within these hybrid proteins and is typically more common at protein termini. Disordered tails are engaged in a wide range of functions, some of which are unique for termini and cannot be found in other disordered parts of a protein. This review covers some of the key functions of disordered protein termini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 129 publications
(173 reference statements)
7
127
0
1
Order By: Relevance
“…The three-to eightfold higher maximum velocity and approximately sixfold greater K m app for Hfq65 suggest that the CTDs limit the numbers of rim sites in each hexamer that are accessible to the RNA. These effects are analogous to autoinhibition in protein kinases and other nucleic acid binding proteins (42), in which partially disordered peptides block substrate recognition. By contrast, Target-A18 seems to be immune to the inhibitory effects of the CTD, being an equally good substrate for full-length Hfq102 and core Hfq65.…”
Section: Resultsmentioning
confidence: 97%
“…The three-to eightfold higher maximum velocity and approximately sixfold greater K m app for Hfq65 suggest that the CTDs limit the numbers of rim sites in each hexamer that are accessible to the RNA. These effects are analogous to autoinhibition in protein kinases and other nucleic acid binding proteins (42), in which partially disordered peptides block substrate recognition. By contrast, Target-A18 seems to be immune to the inhibitory effects of the CTD, being an equally good substrate for full-length Hfq102 and core Hfq65.…”
Section: Resultsmentioning
confidence: 97%
“…[1][2][3][4][5][6][7] Because of their lack of stable structures, exceptional spatiotemporal heterogeneity, outstanding conformational plasticity, ability to be precisely controlled and regulated, and capability to conduct and juggle multiple jobs, intrinsically disordered proteins (IDPs) and hybrid proteins possessing ordered domains and intrinsically disordered protein regions (IDPRs) 8 are specialized in unique biologic functions, [1][2][3][4][5][6][7] which are extending far beyond mostly catalytic activities traditionally assigned to the proteins within the "one gene -one structure -one function" paradigm. 1,3,[10][11][12]18,[39][40][41] In fact, among intrinsic disorder-based biologic functions are regulation of various cellular pathways, binding promiscuity, involvement in diverse signaling processes, and participation in cell protection, protein protection, controlled cell death, and cellular homeostasis. [1][2][3][4][5][6][7] Several recent studies (mostly of computational nature) revealed that IDPs are very common in various proteomes, with the proteome content of IDPs being typically an indicator of both evolution and adaptation to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Biologically active proteins or protein regions that do not assume unique three-dimensional structures by themselves are very common in nature [44 -46] and are abundantly involved in numerous biological processes, where they are found to play different roles in regulation of the function of their binding partners and in promotion of the assembly of supra-molecular complexes [47 -57]. Disorder is unevenly distributed within the protein sequences, and residues located in the protein termini are on the average more disordered than residues in the middle of the protein chain [58]. Among various functions ascribed to such disordered tails are protection of binding sites, stabilization of a protein molecule, and multifarious interactions with various binding partners [58].…”
Section: Homentioning
confidence: 99%
“…Disorder is unevenly distributed within the protein sequences, and residues located in the protein termini are on the average more disordered than residues in the middle of the protein chain [58]. Among various functions ascribed to such disordered tails are protection of binding sites, stabilization of a protein molecule, and multifarious interactions with various binding partners [58]. A function potentially related to this study is their ability to serve as entropic bristles, which by random movements about their point of attachment, would sweep out a significant region in space and entropically exclude large particles without excluding small molecules, therefore acting as entropic bristles or entropic bristle domains [59].…”
Section: Homentioning
confidence: 99%